The Leader as Catalyst: On Leadership and the Mechanics of Institutional Change - Sumon Majumdar; Sharun Mukand (Queen's University, Department of Economics, 2007)
Individual leaders have been central to the transformation of organizations, political institutions and many instances of social and economic reform. In this paper we take a first step towards analyzing the role of leadership to ask: when and how does a leader engineer change? We show that while underlying structural conditions and institutions are important, there is an independent first-order role for individual agency in bringing about change and thus transforming the institutions. We emphasize the key nature of the symbiotic relationship between followers decisions' to willingly entrust their faith in the leader and the leader's initiative at leading them. This two-way interaction can endogenously give rise to threshold effects; slight differences in the leader's ability or the underlying structural conditions can dramatically improve the prospects for successful change. Given the centrality of this leader-follower relationship, we further explore conditions under which an individual may deliberately prefer to follow an ambitious leader with divergent interests rather than a benevolent one with congruent preferences. Thus by virtue of having followers, both `good' and `bad' leaders may be effective at bringing about change.
Keywords: P41; D72; D78; D83; O43; 330; Leadership; Followers; Change; Führungskräfte; Führungspersönlichkeit; Organisatorischer Wandel; Organisatorischer Wandel; Institutioneller Wandel; Theorie